Talk-based approaches to support people who are distressed by their experience of hearing voices: A scoping review - Burr, Christian; Schnackenberg, Joachim K.; Weidner, Frank (Frontiers in Psychiatry, 2022)
Background The positive effects of both antipsychotic medication and cognitive behavioral therapy in psychosis (CBTp) for people who are distressed by their experience of hearing voices remain limited. As a result, there has been a recent surge in talk-based individual approaches. Many of these continue not to be very well known nor implemented in practice. Some of the approaches may focus more on understanding and dealing constructively with voices, an element that has been identified as potentially helpful by voice hearers. Existing barriers to a wider implementation include both the widespread pathologization of hearing voices and a lack of mental health professionals who have been trained and trusted to carry out these new interventions. Methods This scoping review aimed to identify and describe a current synthesis of talk-based individual approaches for people who hear voices, including studies independently of method of study or approach, diagnosis of voice hearers nor of the professional background of interventionists. Results Nine different talk-based approaches were identified. These included: (1) Cognitive Behavioral Therapy for Psychosis (CBTp); (2) AVATAR therapy; (3) Making Sense of Voices (MsV) aka Experience Focused Counselling (EFC); (4) Relating Therapy; (5) Acceptance and Commitment Therapy; (6) Smartphone-based Coping-focused Intervention; (7) Prolonged and Virtual Reality Exposure Therapy; (8) Eye Movement Desensitization and Reprocessing, and (9) Individual Mindfulness-based Program for Voice Hearing. The different approaches differed greatly in relation to the number of sessions, length of time offered and the scientific evidence on efficacy. Psychologists represented the main professional group of interventionists. CBTp and the MsV/EFC approach also included health professionals, like nurses, as implementers. Most of the approaches showed positive outcomes in relation to voice related distress levels. None identified overall or voice specific deteriorations. Conclusion There appears to be a strong case for the implementation of a broader heterogeneity of approaches in practice. This would also be in line with recommendations for recovery focused services and requirements of voice hearers. A greater emphasis on whole systems implementation and thus the involvement of frontline staff, like nurses, in the delivery of these approaches would likely reduce the research-practice implementation gap.